Hubungan Pola Asuh Authoritative dan Self-Efficacy dengan Kepuasan Belajar Siswa Selama Masa Pandemi - Yulisna Ilyas; Nuraini Nuraini; Nefi Darmayanti (Mahesa Research Center, 2022)
The goal of this research is to find out the correlation between the relationship authoritative parenting and self-efficacy with student learning satisfaction during the pandemic. This research is a quantitative research with the population of 255 students of class XI and XII of SMA Swasta Shafiyyatul Amaliyyah Medan. By using random sampling technique obtained a sample of 156 people. The data gathering technique used three scales data: authoritative parenting, self-efficacy, and student learning satisfaction during the pandemic . The Data analysis using multiple regression analysis. Based on the result of research, therefore the conclusion are: 1) There is a significant positive correlation between authoritative parenting and student learning satisfaction during the pandemic. This is indicated by the correlation coefficient = 0.461 with p < 0.05. The coefficient = 0.212, this indicates that the authoritative parenting style contributes 21.2% effectively to student learning satisfaction during the pandemic. 2) There is significant positif correlation between between self-efficacy and student learning satisfaction during the pandemic seen from the correlation coefficient of r xy = 0.603 with p < 0.05, providing an effective contribution of 36.4%. 3). There is a significant positif correlation between authoritative parenting and self-efficacy with student learning satisfaction. This is indicated by the coefficient F reg = 41.931 with p < 0.05, and the correlation coefficient R = 0.631 with p < 0.05 and = 0.398 with a contribution of 39.8%. Based on the research results the hypothesis is accepted.